Evaluation of mechanical, morphological, and biodegradation properties of natural fiber reinforced nano‐biocomposites. (18th January 2022) - Behera, Ajaya Kumar; Das, Nigamananda; Manna, Suvendu
Abstract: Nanoclay modified bio resin‐based jute composites were prepared by thermopressing method to examine the effect of nanoclay on physical, mechanical, and biodegradation properties of jute‐soy composite. Fourier transform infrared spectroscopy of composite was carried out to study the chemical interactions between jute‐soy‐nanoclay, whereas, x‐ray diffractogram and transmission electron microscopic analysis revealed the formation of nanostructure at the composite interface. With 5 wt.% of clay contents, the tensile strength of the composite was 59.2 MPa, which is 65.4% higher than that of the clay‐free jute‐soy composite. The developed composite is thermally stable up to 280°C and increased in weight by only 41.66% after 24‐h water immersion. Inclusion of 5 wt.% nanoclay enhanced storage modulus of nanocomposite from 1170 to 4136 MPa. Evaluation of degradability of composites under compost condition in terms of weight and tensile loss indicated that clay reinforced composites are more durable than jute‐soy composite. Overall, a biodegradable composite material was developed which may be applied as nondegradable plastic alternate in packaging, railway coach, decorating materials, furniture, transport, and construction sector. Abstract :